CATASTROPHIC INJURY INCIDENCE RATES IN SOUTH AFRICAN RUGBY UNION: ARE THERE REGIONAL DIFFERENCES?. Issue 4 (1st February 2017) - Badenhorst, Marelise; Verhagen, Evert; van Mechelen, Willem; Lambert, Mike; Viljoen, Wayne; Readhead, Clint; Baerecke, Gail; Brown, James
Abstract : Background: South Africa has 14 Provincial Rugby regions ('Unions'). Although rugby-related catastrophic injuries have been reported at 2.0 per 100 000 players per year, the comparative risk between each of these SA Unions has not yet been quantified. Understanding the difference in injury risk between Unions is important for potential intervention modifications. Objective: The objective of this study was to compare the catastrophic injury incidence rates between the 14 SA Unions. Design: A prospective, population-based study was conducted across all SA Unions between 2008–2014. Setting: The number of verified players (males and females; under-seven age group to adult; amateur and professional) in each Union was obtained from SA Rugby's 2013 Census. Patients (or Participants): Catastrophic injuries were analysed using BokSmart's serious injury database. Interventions (or Assessment of Risk Factors): Union-specific injury incidence rates with 95% Confidence Intervals were calculated. Catastrophic injuries (Acute Spinal Cord Injuries (ASCI) and Traumatic Brain Injuries (TBI)) within Unions were compared statistically using a Poisson regression with Incidence Rate Ratios (IRR) and a 95% level of confidence (p<0.05). Results: Catastrophic injury incidence rates per Union ranged from 1.8 per 100 000 players (95% CI: 0.0 to 6.5) to 7.9 (95%CI: 0.0 to 28.5). The Union with the highest incidence rate of permanent outcome ASCIs was reported at 7.1 per 100 000 players (95% CI: 0.0 to 17.6). Compared to this Union, five (n=5/14, 36%) of the Unions had significantly lower injury incidence rates of ASCI. Conclusions: Regional differences in catastrophic injury incidence rates exist in SA and interventions should be tailored accordingly. Future studies should investigate the underlying reasons contributing to these regional differences.